Membangun Ketangguhan Mental pada Atlit Muda Petanque - Nurhasan, Nurhasan; Erta, Erta; Hapsari Shinta Citra Puspita Dewi (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
Mental toughness training is an important requirement for young Petanque athletes, given that this sport demands high concentration, emotional stability, and the ability to respond quickly and appropriately to competitive pressure. This community service program aims to improve the psychological abilities of young athletes through training focused on anxiety management, strengthening focus, developing a positive mindset, and increasing self-confidence. The training method was conducted classically through the delivery of material and direct practice designed according to the psychological needs of FOPI East Java athletes. The evaluation of the training results showed an increase in mental toughness, reflected in the athletes' ability to cope with the pressure of competition, maintain calm, and maintain concentration in competitive situations. The athletes also showed an increase in mental preparedness, a more stable response to pressure, and a more positive mindset towards their abilities. These results indicate that psychological intervention through mental resilience training plays an important role in supporting the performance of Petanque athletes, while also serving as the basis for the development of follow-up programs that focus on mental aspects as an integral part of performance development. This program makes a significant contribution to the character building and competitive readiness of young athletes on an ongoing basis.